Duodenal Gossy Piboma-An Unusual Presentation - Iqbal, Sidra; Faheem, Aftab; Gul, Zara; Qureshi, Aneeqa Nasir; Munir, Shahid; Khan, Muhammad Numan; Ali, Usman; Ali, Muhammad Haider (Indus Journal of Bioscience Research, 2025)
Gossypiboma refers to a lump formed by a cotton sponge which is left accidentally in the patient's body during a surgical procedure. Migration of gossypiboma can occur in the digestive tract, diaphragm,urinary bladder and near the vagina.It is most commonly removed through surgical excision. The symptoms include vomiting, pain, dyspepsia, weight loss, swelling and obstruction. The author presents a case of duodenal ulcer caused by the migration of gossypiboma. Case Outline: We present a case of a 28 years old female patient who complained about pain in the epigastric area with vomiting, dyspepsia and weight loss. The patient had underwent an open cholecystectomy few months back and had developed complaints right after that. An intraluminal migration of gossypiboma was found near the duodenum. Surgical intervention successfully removed the gauze, More over a laparotomy and a deudonal repair was performed. Conclusion: In conclusion, it should be considered that a Gossy piboma can be expected in a patient complaining about post-operative pain. Gossypiboma in the duodenum is a rare phenomenon. It is best diagnosed through radiography, endoscopy. MRI and CT scan. A gossypiboma disintegrating the duodenum and causing pyloric stenosis was reported in this case. According to the literature, the chief symptom for an emergency surgical procedure includes “obstruction”. Since there was a pyloric stenosis in this case, so it required an emergent removal. In all cases presenting with an incidental mass, Gossypiboma be kept in the differential diagnosis. Awareness regarding this condition must be carried out to help diagnose such a rare condition. While performing a surgical procedure one should make sure that no sponge or any other medical instrument be left inside the patients body that can lead to serious medico legal repercussions.